ANALYSIS TINGKAT KEPUASAN PELAYANAN NASABAH BSI DI ACEH DENGAN MENGUNAKAN PENDEKATAN IMPORTANCE PERFORMANCE ANALYSIS - Sri Rahayu (Universitas Muhammadiyah Bengkulu, 2022)
The purpose of this research is to analyze service quality and determine customer satisfaction. The method used in this research is to find a quantitative method. The population used in this study are Indonesian Islamic Bank customers who are in the Aceh region. The number of samples used in this study were 188 respondents. primary data is the type of data used in this study. The method used in this research is the Importance Performance Analysis (IPA) method to find out which attributes should be improved and applied. The results of this study use the IPA analysis method which shows that there are 5 service attributes that are in the first quadrant, meaning that there are 5 services that must be improved and improved, because these attributes have unsatisfactory service capabilities for customers and are considered important by customers. From the results of this study, Indonesian Islamic Banks must improve and pay attention to all attributes that are considered lacking and need to be improved in order to increase customer satisfaction in terms of service.Ã‚Â Keywords: satisfaction, service Quality, importance performance analysis